2021
DOI: 10.1186/s12870-021-02874-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale comparative transcriptome analysis reveals key genes and metabolic reprogramming processes associated with oil palm fruit abscission

Abstract: Background Fruit abscission depends on cell separation that occurs within specialized cell layers that constitute an abscission zone (AZ). To determine the mechanisms of fleshy fruit abscission of the monocot oil palm (Elaeis guineensis Jacq.) compared with other abscission systems, we performed multi-scale comparative transcriptome analyses on fruit targeting the developing primary AZ and adjacent tissues. Results Combining between-tissue developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 136 publications
(187 reference statements)
4
12
1
Order By: Relevance
“…This study also provides a unique opportunity to compare the molecular basis of ripe fruit abscission of the two species of oil palm, E. guineensis from Africa and E. oleifera from South and Central America. Notably, a total of six DEGs identified in the current study of E. oleifera were common to those found in the previous study of E. guineensis [11]. These DEGs are particularly relevant, given the differences in the criteria used for screening for DEG candidates in the two studies: the use of a non-shedding individual for the E. oleifera study and the use of a large-scale, multifaceted analysis of ripe fruit AZ induced by ethylene with E. guineensis [11].…”
Section: A Comparison Of E Oleifera and E Guineensis Suggests Abscission Processes Related To Environmental Stress And Epigenetic Modificsupporting
confidence: 66%
See 4 more Smart Citations
“…This study also provides a unique opportunity to compare the molecular basis of ripe fruit abscission of the two species of oil palm, E. guineensis from Africa and E. oleifera from South and Central America. Notably, a total of six DEGs identified in the current study of E. oleifera were common to those found in the previous study of E. guineensis [11]. These DEGs are particularly relevant, given the differences in the criteria used for screening for DEG candidates in the two studies: the use of a non-shedding individual for the E. oleifera study and the use of a large-scale, multifaceted analysis of ripe fruit AZ induced by ethylene with E. guineensis [11].…”
Section: A Comparison Of E Oleifera and E Guineensis Suggests Abscission Processes Related To Environmental Stress And Epigenetic Modificsupporting
confidence: 66%
“…To compare E. oleifera fruit abscission with what is known about ripe fruit abscission in E. guineensis, we compared the DEG list identified in the current study with those found in a recent transcriptome study of E. guineensis [11]. In total, there were six DEGs found in common from the two analyses (Table 1).…”
Section: Comparison With E Guineensis Ripe Fruit Az Transcriptomementioning
confidence: 99%
See 3 more Smart Citations